A relação da dinâmica populacional de Assis Chateaubriand com a modernização da agricultura e apropriação da terra - Lorensetti, Everaldo (2017)
This research looks for comprehend the population dynamics of the Assis Chateaubriand city, located in the West of the State of Paraná, considering the land tenure and the modernization of agriculture. The creation of the Assis Chateaubriand city, in 1966, and the news broadcast nationally by Journalist's communication tools, that gave the name to the city, they attracted migrants from all over the country in search of land and work. The arrival of migrants made the population of the city appears as the eighth largest in Paraná, in the 1970 census, four years after the emancipation of the city. But the permanence of the migrant population in the city did not occur in view of the difficulties of access to land, in the first moment and in the process of agriculture’s modernization. In this sense, it had an expulsion and expropriation of many families that migrated to other regions of Brazil, as well as to urban and industrialized centers, what registered in the history of the freshly created city, one of the largest events of populational withdrawal.